2020
DOI: 10.33626/inovasi.v17i1.182
|View full text |Cite
|
Sign up to set email alerts
|

Penentuan Teknologi Tepat Guna Pemanfaatan Biomassa Kelapa Sawit untuk Pekebun Rakyat Skala UMKM di Sumatera Utara Menggunakan Pendekatan BOCR-AHP

Abstract: Keberadaan usaha kebun kelapa sawit yang dikelola pekebun umumnya masih terbatas pada usaha penjualan tandan buah segar (TBS) dan simpan pinjam. Ketergantungan pada penjualan TBS tersebut memiliki resiko yang besar terhadap fluktuasi harga yang pada akhirnya berpengaruh terhadap kinerja usaha kebun. Pemanfaatan biomassa kelapa sawit dapat menjadi salah satu peluang usaha yang menjanjikan bagi pekebun sawit serta mendukung ketahanan pangan dan energi masyarakat di pedesaan. Penelitian bertujuan untuk menentukan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Several studies on AHP have been carried out relating to human resource development, which is applied in the selection of prospective employees of the company (Yani & Yuniarti, 2019), employee salary determination (Mardika, 2021), and institutional performance measurement (Lestari et al, 2020;Santika & Lestari, 2021). In addition, there is also research on applying AHP in technology development, such as determining appropriate technology (Nasution, 2020) and superior product development (Hayat et al, 2019). Based on previous studies, the application of AHP has not been found in implementing the reward system on employee performance.…”
Section: A Introductionmentioning
confidence: 99%
“…Several studies on AHP have been carried out relating to human resource development, which is applied in the selection of prospective employees of the company (Yani & Yuniarti, 2019), employee salary determination (Mardika, 2021), and institutional performance measurement (Lestari et al, 2020;Santika & Lestari, 2021). In addition, there is also research on applying AHP in technology development, such as determining appropriate technology (Nasution, 2020) and superior product development (Hayat et al, 2019). Based on previous studies, the application of AHP has not been found in implementing the reward system on employee performance.…”
Section: A Introductionmentioning
confidence: 99%